Gaining competitiveness through trust: the experience of Russia. (31st January 2008) - Kuznetsov, Andrei; Kuznetsova, Olga
This paper seeks to reveal the potential of the concept of national competitiveness as a practical analytical tool. The paper offers suggestions on how research on national competitiveness can contribute to setting targets for socio-economic agenda in transition economies with special focus on Russia. We start by stressing the importance of the institutional context as an element of national competitiveness and then concentrate on generalised trust. We analyse the situation with generalised trust in modern Russia and suggest that the development of corporate social responsibility is the most credible remedy for the deficiency of trust and, eventually, to competitiveness, in the short term.